Masonry Buildings: Research and Practice - Rodrigues, Hugo (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Masonry is a construction material that has been used throughout the years as a structural or non-structural component in buildings. Masonry can be described as a composite material made up of different units and diverse types of arrangements, with or without mortar, that is used in many ancient public buildings, as well as with the latest technologies being applied in construction. Research in multiple relevant fields, as well as crossing structural with non-structural needs, is crucial for understanding the qualities of existent buildings and to develop new products and construction technologies. This book addresses and promotes the discussion related to the different topics addressing the use of masonry in the construction sciences and in practice, including theory and research, numerical approaches and technical applications in new works, and repair actions and interventions in the built environment, connecting theory and application across topics from academia to industry.